2010
DOI: 10.1089/lap.2010.0010
|View full text |Cite
|
Sign up to set email alerts
|

Which Is the Best Vessel-Sealing Method for Pediatric Thoracoscopic Lobectomy?

Abstract: Based on our early experience and a review of the literature, we believe TLL is a feasible and technically reproducible approach that avoids the inherent morbidity of a major thoracotomy incision. Bleeding should not be the main argument to decide in favor of a thoracotomy. LigaSure's reliability would depend on vascular diameter and on patient age. VIs can be prevented in older children by using the sealing device and a proximal Hem-o-Lok clip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Bipolar (Ligasure, Valleylab Inc., Boulder, CO) and ultrasonic (Harmonic Scalpel, Ethicon Endosurgery Inc., Cincinnati, OH) vessel‐sealing devices have been evaluated in rabbit and swine models for sealing lung parenchyma and found to be generally safe and effective with minimal morbidity . These devices have also been used for this purpose in people; however, we are unaware of reports documenting the use of the Ligasure device in dogs for peripheral lung biopsy.…”
mentioning
confidence: 99%
“…Bipolar (Ligasure, Valleylab Inc., Boulder, CO) and ultrasonic (Harmonic Scalpel, Ethicon Endosurgery Inc., Cincinnati, OH) vessel‐sealing devices have been evaluated in rabbit and swine models for sealing lung parenchyma and found to be generally safe and effective with minimal morbidity . These devices have also been used for this purpose in people; however, we are unaware of reports documenting the use of the Ligasure device in dogs for peripheral lung biopsy.…”
mentioning
confidence: 99%
“…The ability of the clips to be placed in an en-bloc fashion will be affected by patient size, specific j o u r n a l o f s u r g i c a l r e s e a r c h 1 9 2 ( 2 0 1 4 ) 6 1 6 e6 2 0 lung lobes affected, and the presence or absence of intercurrent disease that may lead to infection and adhesion formation. If Hem-o-lok clips are too small to affect reasonable closure of the pulmonary hilum it may be possible to use them for vascular and/or bronchial closure after isolation of those structures has been performed [10,11]. In this open thorax model, no assessment of the ease of minimally invasive application between Endo GIA and Hem-o-lok was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…One report describes the use of Hem-o-lok clips for bronchial closure in pediatric VATS lobectomy [10], whereas another describes their use in adult robotic anatomic segmentectomy of the lung [11]. However, to the authors' knowledge there have been no published studies evaluating the bursting pressures for this device when used on a bronchus or in an en-bloc fashion on the pulmonary hilus.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other studies have demonstrated the safety of these clips in ligating the appendiceal stump 3,4 and have advocated its use in hysterectomy, 5 prostatectomy, 6 and lobectomy. 7 The Food and Drug Administration (FDA), however, issued a warning to health care providers that Hem-o-lok clips can pose a serious risk to the donor during a laparoscopic living-donor nephrectomy when used for the ligation and occlusion of the renal artery. 8 The warning followed 15 reports of 12 injuries and 3 deaths that occurred between November 2001 and March 2005.…”
Section: Introductionmentioning
confidence: 99%